The Structure and Factors Affecting the Determination of the Executive Managers Compensation - Bolfek, Berislav; Torbarina, Perina; Surać, Lucija (Oeconomica Jadertina, 2017)
Executive managers represent a small precentage of one companies workers but they are the most important group of employees. The ideal compensation management policy ensures that the best talent will remain with the organization while attracting new talent and minimizing turnover. Executive compensation normally combines base salary, short-term and long-term incentives, benefits and bonuses. The purpose of this paper is to explore and analyse data about stucture and factors that affect executive compensation determination of top five global brands. The collected data on the hight of executive compensations refer to the period from 2010 to 2015. Selected executives are leaders of the companies that are ranked as the top five global brands on Interbrands 2015 list. CEO pay in the U.S. has grown exponentially since the 1970s. The CEO-to-worker pay ratio trend indicates that the ratio keeps rising over the years, with some CEOs making more than 400 times the median salary of their employees. Some analyst recommend that every company’s compensation system should include implementing certain regulatory actions, using different metrics for determining CEO compensation, making board member-CEO relationships transparent to all company stakeholders.